CTNI-31. INTERIM RESULTS OF A PHASE I/IIA STUDY TO EVALUATE THE SAFETY AND EFFICACY OF BBB OPENING WITH THE SONOCLOUD-9 IMPLANTABLE ULTRASOUND DEVICE IN RECURRENT GLIOBLASTOMA PATIENTS PRIOR TO IV CARBOPLATIN. (9th November 2020) - Idbaih, Ahmed; Ducray, François; Stupp, Roger; Baize, Nathalie; Chinot, Olivier; de Groot, John; Guyotat, Jacques; Sonabend, Adam; Menei, Philippe; Dufour, Henry; Weinberg, Jeffrey; Desseaux, Carole; et al.
Abstract: Low intensity pulsed ultrasound (LIPU), in combination with systemic injection of microbubbles, can be used to transiently disrupt the blood-brain barrier (BBB) and increase brain-drug concentrations. In pre-clinical models, carboplatin can be enhanced by a factor of 5x in the brain using LIPU and increase the survival of GBM-bearing mice. In clinical studies, a single emitter, implantable ultrasound device (SonoCloud-1) was used to disrupt the BBB in 19 rGBM patients prior to carboplatin chemotherapy (NCT02253212). The feasibility of this approach was demonstrated, and safe acoustic parameters were determined. The primary objective of this subsequent Phase 1/2a study (NCT03744026) was to demonstrate the safety of BBB disruption over a larger volume, including the tumor and surrounding peritumoral region using a nine-emitter version of the device (SonoCloud-9). This study was a 3 + 3 design using escalating numbers of activated 1-cm diameter emitters (3, 6, 9). GBM patients at any recurrence, with a maximum tumor size of < 70 mm were included. The SonoCloud-9 device was implanted during tumor debulking/resection surgery and replaced the bone flap. The device was activated every four weeks for 270 seconds, concomitantly with DEFINITY ® microbubbles to disrupt the BBB prior to administration of carboplatin. Magnetic resonance imaging was performed to verify safety and the extent of BBB disruption. As of June 2020, the escalation phase of the study (9 patients) was complete, with a median of four monthly cycles of sonication and carboplatin chemotherapy per patient. No DLTs were observed. The overall tolerance of the SonoCloud-9 implant was good, with only a few, transient, and manageable related adverse events. The safety of administration of multiple repeat treatments of BBB opening using nine emitters of the device at an acoustic pressure of 1.03 MPa will be confirmed in an additional 12 patients to be included in the ongoing expansion phase.